(3GdYedjGJ GdJaGhVjIs - (3YHO GdcQje(B, (3cGXes ((3YeGf(B:s (3OGQ GdcfhR GdeYQaI(B,s, 2007)
(3jYJHQ ehVhY GOGQI GdGLJeGYGJ(B((3GdGLJeGY(B) (3ef GdehVhYGJ GdegeI aj JacjQ cKQjf ef GdeOQGA defXeGJge hGdJj JSGYO Ydi Gdhbha Ydi fbGW GdbhI hGdVYa dOi GdeLJeYjf hgPG GdcJGH JVef (B7 (3aUhd cGfJ Ydi GdfMh GdJGdj GOGQI GdGLJeGYGJ , GOGQI GdeDJeQGJ , GdeDJeQ GdGbdjej GdKGfj hGdYTQjf dGaQjbjG hGdGYOGO deDJeQ GdbeI GdYGdejI ddCZPjI , GdeDJeQGJ hGdGQgGH , egGQGJ GdJaGhV , CfhGY GdJaGhV hCSGdjHg , YedjI GdJaGhV YHQ GdKbGaGJ GdeNJdaI s
(3HjHdjhZQGajG U(B.231s
Keywords: (3GOGQI GdGLJeGYGJs; (3GOGQI GdGYeGds; (3eDJeQGJs